Monetary policy and financial stability in a banking economy: Transmission mechanism and policy tradeoffs - Barnea, Emanuel; Landskroner, Yoram; Sokoler, Meir (Journal of Financial Stability, 2015)
The 2008 global financial crisis demonstrated that monetary policy and financial stability policy are more highly interrelated than previously thought. This paper analyzes the interactions between these policies using a non-linear overlapping-generations model with financial frictions in the form of banking financial intermediation. The paper embeds negative externalities due to contagion effects in physical investments which creates the need for financial stability policy. We show how the monetary policy transmission mechanism depends on financial stability policy tools as well as on regulatory and institutional constraints. We find policy tradeoffs in trying to accomplish both monetary and financial stability targets. The central bank must take these tradeoffs into account when selecting the tools in its policy toolbox. Another important finding is the interchangeability of price stability and financial stability policy tools.